2018
DOI: 10.1098/rsob.180026
|View full text |Cite
|
Sign up to set email alerts
|

Roles of glycosaminoglycans as regulators of ligand/receptor complexes

Abstract: Glycosaminoglycans (GAGs) play a widespread role in embryonic development, as deletion of enzymes that contribute to GAG synthesis lead to deficiencies in cell migration and tissue modelling. Despite the biochemical and structural characterization of individual protein/GAG interactions, there is no concept available that links the molecular mechanisms of GAG/protein engagements to tissue development. Here, we focus on the role of GAG polymers in mediating interactions between cell surface receptors and their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 86 publications
1
41
0
Order By: Relevance
“…As example of a target-protein we selected fibroblast growth factor 2 (FGF-2 or basic fibroblast growth factor). Like other FGF family members, FGF-2 is involved in a large number of biological processes in a GAG cofactor-assisted manner [ 16 , 17 ], and a rising amount of evidence has shown that CSs participate and modulate its binding to its FGFR receptor [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As example of a target-protein we selected fibroblast growth factor 2 (FGF-2 or basic fibroblast growth factor). Like other FGF family members, FGF-2 is involved in a large number of biological processes in a GAG cofactor-assisted manner [ 16 , 17 ], and a rising amount of evidence has shown that CSs participate and modulate its binding to its FGFR receptor [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have multiple structural and mechanical roles. GAG polymer acts as an activator that facilitates interaction between receptor/ligand complexes and triggers cell signaling (Smock & Meijers, 2018). Enzymatic GAG depolymerization activates CXCL8-induced endothelial downstream signaling that related to changes in endothelial proteins such as Zyxin and Caldesmon which contribute to the cytoskeletal organization, cell adhesion, and cell mobility (Derler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Because Reelin and CSPGs are both expressed in the extracellular space of the MZ (Nichols and Olson, 2010), it is possible that Reelin and CSPGs interact directly to modulate receptor binding activity (Smock and Meijers, 2018). To first determine whether Reelin-dependent Dab1 phosphorylation occurs in the presence of CSPGs, we examined Dab1 phosphorylation status.…”
Section: Reelin Signaling Reverses Cspg-induced Akt Dephosphorylationmentioning
confidence: 99%
“…CSPGs may inhibit neurite growth by acting as an anti-adhesive substrate (Emerling and Lander, 1996), but specific signaling events have also been demonstrated. For example, subsets of CSPGs are known to bind and augment the signaling of other compounds in the nECM (Smock and Meijers, 2018). In addition, some CSPGs have been shown to directly bind and activate receptors such as receptor tyrosine phosphatase s (RPTPs ) and leukocyte common antigen-related phosphatase (LAR), which are known to functionally inhibit axonal regeneration (Fisher et al, 2011;Lang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%